EFISIENSI, EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH DI KABUPATEN MANOKWARI - Mallisa, Mini Susi; Sudarwadi, Hustianto; Mamoribo, Yubelina Y. H. (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2023)
This research aims to determine the level of efficiency, effectiveness and contribution of Urban and Rural Land and Building Tax (PBB-P2) to Original Regional Income (PAD) revenues in Manokwari Regency in 2018-2021. The method used in this research is a quantitative descriptive approach. The results of this research conclude that the efficiency level of PBB-P2 revenue in Manokwari Regency from 2018-2021 was very efficient, then the level of effectiveness of PBB-P2 revenue in 2018-2021 experienced insignificant fluctuations or fluctuated with an average percentage of 108. 99% with very effective criteria and the level of contribution of PBB-P2 revenue to Manokwari Regency's PAD in 2018-2021 shows the criteria value is very low with an average percentage of 6.05%, the level of contribution is decreasing every year, this is because the realization of PAD is always increases every year, but the realization of PBB-P2 is fluctuating. Keywords: Land and Building Tax, Regional Original Income, Tax Contribution